Thermal energy storage via waste heat from finned heater by using different phase change materials in a closed space - Öztop, Hakan Fehmi; Cosanay, Hakan; Biswas, Nirmalendu; Selimefendigil, Fatih (Elsevier, 2023)
In this study, a numerical analysis of the melting of phase change materials (PCMs), is analyzed in a closed space, which is heated from the bottom wall. The heater has a set of fins with constant geometry, placed on the bottom heated wall. The closed space has also two rectangular-shaped containers (placed horizontally), which are attached to the vertical walls at different dimensions and locations. Each of the containers has different types of PCMs, which receive waste heat from the fins. The performance analysis of the combined system is carried out by solving governing equations using the finite volume technique was used to solve the transport equations. The thermal performance of the composite system is assessed for the wide range of geometrical parameters such as length ratios of the fins (Lp), height ratios (c/H), and flow control parameters such as Grashof numbers (Gr). The result showed that the inclusion of PCM containers can effectively utilize the waste heat and can modulate the thermal transport process significantly. The position and size of the fins significantly alter the convective process inside the enclosure. The flow structure shows asymmetric features due to the obstruction by the fins attached to the vertical walls. Too much closure position of the PCM-filled longer fins to the fins assembly leads to the multicellular vortices like 'Be & PRIME;nard cell' due to the strong temperature gradient between the two sets of fins. For the long fins, too much closure position reduces the total melting time. The usage of PCM 2 is always beneficial for faster acclimation energy due to fast melting for any length and position of the fins. Different phase change materials and their melting behaviors are studied first time in this work to get cooling effect of a finned heating system, which is the main originality and the work. Such a concept could be adopted as thermal energy storage (TES) system, which can benefit the reduction in energy losses.
Keywords: Phase change material (PCM); Thermal energy storage (TES); Fin; Melting behavior; Heat transfer